Weston's Westons portraits and nudes - Stebbins, Theodore E. Jr (Museum of Fine Arts, 1989)
Seventy full-size plates and seventy-five smaller illustrations, all reproduced in tritone plus tinted varnish, convey the subtlety and power of the extraordinary figurative work of Edward Weston (1886-1958). This is the first major publication focusing solely upon his portraiture and nudes, offering new insights into the breadth and quality of Weston's considerable achievement. The book was published on the occasion of a major traveling exhibition of Weston's portraits and nudes organized by the Museum of Fine Arts, Boston. All the prints are drawn from the collection of William H. Lane, who acquired them from the heirs of Edward Weston.